Crop Productivity and Global Food Security Nexus in the face of Climate Change: Sustainable Pathways to a Green Economy in Ghana - Konyannik, Benjamin Yennuna; Jessica Ampah-Korsah,; Adubofour Kofi Adusei,; Musah Fuseini,; Vida A.S.A. Ezeh,; Michael Amponsah,; Gilbert Osei,; Elvis Vitorsu,; Samuel Yennukua Konlan, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2025)
Climate change constitutes a substantial threat to food security globally, and Ghana, as a development nation, is not immune to this menace. Rising temperatures, changing precipitation patterns, and increased frequency of extreme weather events are impacting crop productivity, water availability, and food quality. This review synthesizes current studies on climate change impacts on crop productivity and food security in Ghana, identifying knowledge gaps and areas for further research. Ghana's agricultural sector is highly susceptible to climate change, with potential yield declines of 2.8%, 2.6%, and 2.4% for rice, maize, and wheat, respectively, for every 1°C temperature increase. The study projects significant economic losses, increased poverty, and food insecurity, emphasizing the need for urgent action to implement climate-resilient agriculture practices. The study explored adaptation strategies, including genome-based approaches, climate-smart agriculture practices, artificial intelligence, nanotechnology, and strategic irrigation management, which can be integrated to promote sustainable agriculture and enhance food security. Ghana faces challenges in addressing climate change, including limited funding and lack of comprehensive climate change law, but has committed to reducing greenhouse gas emissions by 30% by 2030 by presenting its updated Nationally Determined Contributions (NDCs). The findings inform evidence-based policymaking, aligning with the United Nations' Sustainable Development Goals (SDGs), particularly Goal 2 (Zero Hunger), Goal 6 (Clean Water and Sanitation), and Goal 13 (Climate Action). This study provides a foundation for further research and policy development to address the pressing issue of climate change and food security in Ghana.